Application of perennial legume green manures to improve growth and yield of organic lowland rice - M Winarni; P Yudono; D Indradewa; B H Sunarminto (Journal of Degraded and Mining Lands Management, 2016)
A pot experiment in green house was done to study the effect of the dosage and speciesof perennial legume green manures to the physiological traits, growth and yield of organic lowland rice (Oryza sativaL.), and to obtain the optimal dosage as well.  The research was arranged in a factorial randomized block design consistedof two factors with three replications.The first factor was the species of perennial legume thatconsisted of threespecies: Turi (Sesbaniagrandiflora), Glirisidia (Gliricidiasepium), and Lamtoro (Leucaenaleucocephala) and cow manure as control treatment. The second factor was the dosage of green manure thatconsisted of four levels: 5, 10, 20 and 40 t/ha.  The results showed that application ofperennial legumesinto the soil significantly improved the growth and yield of rice.  The application of  20 t Glirisidia leaves/haproduced the highest grain yield, followed by 20 t Lamtoro leaves/ha and 20 t Turi leaves/ha.  The optimal dosages of S. grandiflora, G. sepium and L. leucochepala leaves that could yield 58.03 g/hill (equivalent to14.51 t/ha), 53.67 g/hill (equivalent to 13.42 t/ha), and 49.67 g/hill (equivalent to 12.42 t/ha) were 28.05, 25.46 and 26.41 t/ha, respectively.